Spirituality in health care and the industrial workplace (2012)
"Spirituality, with many and varied definitions, plays many useful roles in clients' lives. In health care settings, it is effective in enhancing physical and mental health, in reducing symptoms of illness, in coping with illness, in treatment and recovery from illness. Similarly, in industrial organizations, spirituality helps to improve employees' performance, organizational effectiveness, support organizational performances enhance employees' well-being, provides them with the sense of meaning at work and a sense of interconnectedness. In view of the above, the, paper explains the meaning of spirituality, and explains its positive contributions to health and industrial welfare. The paper concludes that when the health care and industrial workplace spirituality is properly understood by health care-givers and industrial welfare officers they will be adequately equipped to meet the spiritual challenges of their patients or clients. Also, they will be able to identify the clients' spiritual beliefs and strengths that motivate them in the healing process or to improve their productivity at the workplace. "